A Review of the Impact of Neuter Status on Expression of Inherited Conditions in Dogs - Oberbauer, Anita M.; Belanger, Janelle M.; Famula, Thomas R. (Frontiers in Veterinary Science, 2019)
Gonadectomy is an important reproductive management tool employed in many countries, and is highly prevalent in the US with an estimated 85% of dogs being neutered. Despite the societal benefits in pet population control, negative associations between neuter status and health conditions have been reported in recent years. Most particularly observed are the consequences of early age neutering. Knowing that different physiological systems rely upon gonadal steroids during development and physiological maintenance, studies have been undertaken to assess the impact of neuter status on multiple body and organ systems. For some inherited conditions, neutering is associated with an increased risk of expression. Neutering has also been associated with altered metabolism and a predisposition for weight gain in dogs, which may confound the detected risk association between neutering and disease expression. This review summarizes the effects of neutering on inherited conditions and also explores the potentially exacerbating factor of body weight.